Copper affects steroidogenesis and viability of human adrenocortical carcinoma (NCI-H295R) cell line in vitro. Issue 9 (28th July 2020) - Bilcikova, Jana; Fialkova, Veronika; Duranova, Hana; Kovacikova, Eva; Forgacs, Zsolt; Gren, Agnieszka; Massanyi, Peter; Lukac, Norbert; Roychoudhury, Shubhadeep; Knazicka, Zuzana
Abstract: Copper is an environmental risk factor, which has various effects on reproductive endocrinology. In this study human adrenocortical carcinoma (NCI-H295R) cell line was used as an in vitro biological model to study the effect of copper sulfate (CuSO4 .5H2 O) on steroidogenesis and cytotoxicity. The cell cultures were exposed to different concentrations (3.90, 62.50, 250, 500, 1000 µM) of CuSO4 .5H2 O and compared to control group (medium without CuSO4 .5H2 O). Cell viability was measured by the metabolic activity assay. Quantification of sexual steroid production directly from the medium was performed by ELISA assay. Following 48 h culture of NCI-H295R cell line in the presence of CuSO4 .5H2 O a dose-dependent depletion of progesterone release was observed even at the lower concentrations of CuSO4 .5H2 O. The lowest levels of progesterone were detected in groups with the higher doses (≥ 250 µM) of CuSO4 .5H2 O, which elicited significant cytotoxic action. Testosterone production decreased significantly, and this decline was more prominent in comparison to that of progesterone. The lowest release of testosterone was recorded at 1000 µM of CuSO4 .5H2 O. The cytotoxic effect of CuSO4 .5H2 O was evident at all concentrations used in the study. The presented data suggest that copper has detrimental effects on sexual steroid hormones and consecutively on reproductive physiology.